Microstructural modifications induced in Si+-implanted yttria-stabilised zirconia: a combined RBS-C, XRD and Raman investigation. Issue 10 (1st March 2022) - Mikšová, Romana; Malinský, Petr; Cutroneo, Mariapompea; Holý, Václav; Sofer, Zdeněk; Cajzl, Jakub; Debelle, Aurélien; Nowicki, Lech; Macková, Anna
Abstract : The structural differences in (100)-, (110)- and (111)-oriented cubic yttria-stabilised zirconia (YSZ) single crystals after implantation with 2 MeV Si + ions at the fluences of 5 × 10 15, 1 × 10 16 and 5 × 10 16 cm −2 were studied using Rutherford backscattering spectrometry in the channelling mode (RBS-C), using X-ray diffraction (XRD) and Raman spectroscopy. Abstract : The structural differences in (100)-, (110)- and (111)-oriented cubic yttria-stabilised zirconia (YSZ) single crystals after implantation with 2 MeV Si + ions at the fluences of 5 × 10 15, 1 × 10 16 and 5 × 10 16 cm −2 were studied using Rutherford backscattering spectrometry in the channelling mode (RBS-C), X-ray diffraction (XRD) and Raman spectroscopy. The RBS-C results show that the damage accumulation in the 〈110〉 direction exhibits a lower level of disorder (<0.3) than the other orientations (<0.6) and it seems that the (110) crystallographic orientation is the most resistant to radiation damage. The experimental results from the RBS measurement were compared with the results from the XRD measurements. The XRD data were analysed using the standard two-beam dynamical X-ray diffraction theory and the pure isotropic strain was deduced from the fit for the fluence of 5 × 10 15 cm −2 . It was shown that the maximum value of the isotropic strain does not depend on the surface orientation. The increase in signal intensity at ∼689 cm −1 is probably related to an increase in implantation defects such as oxygen vacancies.